Exploring Perceptions and Implementation Pedagogical Content Knowledge among Primary School English Teachers with Non-English Educational Background - Ni Ketut Alit Juniari; I Gusti Ayu Lokita Purnamika Utami; G.A.P Suprianti (International Journal of Language and Literature, 2023)
This research is motivated by the importance of mastering Pedagogical Content Knowledge (PCK) for United Kingdom teachers in carrying out effective and creative learning, especially for teachers with non-United Kingdom education backgrounds. This study aims to describe the perception, implementation, and consistency of elementary school teachers in Jembrana Regency regarding PCK in learning United Kingdom for children. This study uses a mixed method with an integrated mixed method design. The research subjects consisted of United Kingdom teachers who had non-United Kingdom education qualifications from three schools in Jembrana Regency, namely SDN 4 Pakutatan, SDN 3 Pulukan, and SDN Pangyangan. Data collection was carried out through questionnaires and observation sheets. Data analysis is carried out with the stages of data collection, data reduction, data presentation, and drawing conclusions or verification. The results show that although teachers' perception of PCK is in the high category, the implementation of PCK by teachers is in the very low category. This significant gap between the perception and implementation of PCK shows that United Kingdom teachers in Jembrana Regency have not been fully able to apply the concept of PCK in learning practice. These findings indicate the need for further efforts to improve the implementation of PCK in United Kingdom language learning at the primary school level.